Bicistronic expression strategy for high‐level expression of recombinant proteins in Corynebacterium glutamicum. Issue 10 (14th August 2017) - Liu, Xiuxia; Zhao, Zihao; Zhang, Wei; Sun, Yang; Yang, Yankun; Bai, Zhonghu
Abstract: Directly using the promoter associated with 5′‐untranslated region of a high‐protein‐abundance gene from the genome may cause low expression activity of an expression system. A bicistronic expression part containing the short 5′ coding sequence of the source gene and an embedded Shine–Dalgarno sequence can cause higher expression levels of the recombinant gene in a bicistronic cassette. Here, we evaluated two methods to construct expression parts and exploited genomic sequence sources to provide specific functional sequences to complete the expression system. The architecture of the bicistronic part increased the expression levels of target genes and performed more reliably than conventional expression parts with the same promoter and 5′ untranslated region. For Corynebacterium glutamicum, the strongest bicistronic part, HP‐BEP4, was obtained from a heterologous sequence source, leading to a 2.24‐fold increase in the expression level of fluorescent protein over constitutively expressed pXMJ19 or the production of more than 100 mg/L single‐chain variable fragment (scFv). It could meet the needs of overexpressing key genes in C. glutamicum .